math

posted by .

determine the inverse, f^-1, of f when f(x)= 5-2x^3

  • math -

    y = 5 - 2 x^3
    2x^3 = 5-y
    x = [(5-y)/2]^1/3

    f^-1(x) = [(5-x)/2]^1/3 is the inverse function. Plugging in f(x) gives you back x.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). Use finite differences to determine the equation of the function. (b) Draw the graph of the function. (c) Draw the inverse on the graph. (d) Show at least two different …
  2. Math

    Determine whether each equation is true for all x for which both sides of the equation are defined. If it is true, support your conclusion with a sketch using the unit circle. If it is false, give a counterexample. inverse sin(-x)=-inverse …
  3. math

    Determine the inverse of f(x)=(x^3)-2 Is the inverse the switch of coordinates between x and y or is it 1 over the whole equation?
  4. Inverse functions

    Solve for y to determine the inverse y=2-(1/2x)
  5. Math 3

    Find the inverse of the function f(x) = 5 – e^(x-1). Determine the domain, range, and asymptotes of the function and its inverse function. Please show all of your work.
  6. precalculus

    find the inverse of the function, graph the inverse function, determine the domain, range and asympotoes f(x)= e^-x/(2)+4
  7. pre calculus

    Find the inverse of the function below. Graph the function below and the inverse. Determine the domain, range and asymptotes of the function below and the inverse function. Please show all your work. f(x) = 2e^-x + 5 Just looking at …
  8. Advanced Algebra

    What is the inverse of each of the functions defined by the following equations, if the inverse exists. If the inverse does not exist for the largest possible domain, limit the domain so that the inverse will exist. In each case, give …
  9. Calculus

    If g(X) = 2+ln(x-5), find the inverse function, (g^(-1))(x) Solution: y = 2+ ln(x-5) e^y = 2 + x - 5 x = e^y + 3 y = e^x + 3 g^(-1) = y = e^x + 3 Is that right?
  10. Math

    A square matrix A= (5 4 2 3 1 3 -2 -1) Determine the determinant of A(detA) Determine the inverse of A (A-1)

More Similar Questions